PM2.5-bound trace metals within vicinity of a coal-fired power plant: source apportionment and health risk assessment - Sufian Abd Rahman; Muhammad Ikram A Wahab; Nor Fadilah Rajab; Mohd Talib Latif (Penerbit Universiti Kebangsaan Malaysia, 2025)
A coal-fired power plant is an industry known for its environmental health effects due to emissions containing pollutants like PM2.5. Studies show PM2.5 contains multiple hazardous pollutants, including metals. This study was conducted in Klang, Malaysia, to assess the concentration of trace metals in PM2.5 near a coal-fired power plant, identify their sources, and evaluate human health risks. The average PM2.5 concentration was 14.42 ± 8.7 μg/m³, with maximum levels (43.15 μg/m³) exceeding the Malaysian Ambient Air Quality Standard. PM2.5 samples were collected from June to November 2018 and extracted using sonication in ultrapure water. Eighteen trace metals were analysed using ICP-MS, and the results were used for Principal Component Analysis (PCA) for source identification. PCA showed that the trace metals originated from sea salt and biomass burning (37%), coal combustion and vehicular emissions (34%), oil combustion (17%), and soil dust (12%). A health risk assessment (HRA) for selected metals indicated that carcinogenic and non-carcinogenic risks were generally within acceptable limits. However, the Hazard Quotient (HQ) for nickel exceeded the acceptable limit at one point (HQmax = 2.24). A limitation of this study is that its sampling period was confined to the southwest monsoon and intermonsoon seasons, so the findings may not be representative of the entire year. The findings highlight the importance of managing industrial emissions to improve air quality, aligning with UN Sustainable Development Goals for Affordable and Clean Energy (SDG 7) and Climate Action (SDG 13).